A Critical Literature Review of Indonesian Senior High School Students’ Interest in Physics Learning - Nurjannah, Anggi; Purba, Cindy Picelia Alvoni; Panjaitan, Ida Roasih; Sinaga, Karina Angely; Ritonga, Karyn Arme Septia Br; Sinaga, Maria Putri; Panggabean, Deo Demonta (Lensa: Jurnal Kependidikan Fisika, 2025)
Student interest in physics at the Indonesian senior-high-school (SMA) level remains a pivotal yet uneven driver of science achievement. This study offers a critical narrative review of 15 peer-reviewed national articles published between 2018 and 2024 to identify the factors that foster—or inhibit—students’ engagement with physics. Systematic searches of Garuda, SINTA, Google Scholar, and ERIC yielded empirical studies that met five inclusion criteria; data were extracted, quality-appraised with a CASP-based checklist, and thematically coded. Results indicate that a majority of learners report good to very good interest, but this enthusiasm is fragile, undermined by persistent perceptions of physics as abstract, difficult, and only loosely connected to everyday life. Influences cluster into internal factors—motivation, self-efficacy, prior knowledge—and external factors—pedagogical design, facility availability, and learning climate. Evidence converges on three high-leverage practices: blended-learning models that combine face-to-face inquiry with digital simulations; context-rich tasks linking concepts to household technologies and socio-scientific issues; and explicit scaffolding of critical-thinking routines. Conversely, lecture-dominated instruction and limited laboratory access correlate with lower interest and higher difficulty indices. The review recommends that teachers embed interactive digital media and real-world problem contexts, while policy-makers invest in virtual-laboratory infrastructure, equitable internet connectivity, and ongoing professional development targeting inquiry facilitation and formative assessment of reasoning. Future research employing large-scale quantitative designs across diverse regions is needed to validate these recommendations and refine a national strategy for sustaining students’ curiosity and achievement in physics.